(3GdCQHYhf GdYhGdis - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s ((3jhSa Hf ZjHi Hf VjGA GdOjf s)
(3ChdgG (B:s
(3bGd GdTjN EeGe GdCFeI GdeLJgOjf s
(3BNQgG (B:s
(3JeJ GdCMGOjK GdCQHYhf GdYdjGq s
(3HBNQgG ELGRI HbQGAI GdbQBf HGdbQGAGJ GdYTQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B45 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B291s
Keywords: (3GdMOjK h GdeUWdMs